The Scientific American brave new brain - Horstman, Judith (San Francisco, Calif. : Jossey-Bass, 2010)
Judith Horstman presents a highly informative and entertaining look at the future of your brain, based on articles from Scientific American and Scientific American Mind magazines, and the work of today's visionary neuroscientists. --from publisher description
Incluye referencias bibliográficas (p.143-151) e índices.
Keywords: NEUROFISIOLOGIA; NEUROCIENCIAS; CEREBRO -- METABOLISMO; CEREBRO -- FISIOLOGIA; SISTEMA NERVIOSO